Evaluation of an Audiovisual Educational Tool with Reinforcement Messages for Orthodontic Patients: A 6-Month Randomized Controlled Trial - Restrepo Quijano, Laura; Vasco Gomez, Maria Paula; Hurtado Velasquez, Natalia; Benitez Moreno, Luis Fabian (UI Scholars Hub, 2026)
Background: Orthodontic treatment increases the risk of bacterial plaque accumulation; therefore, oral hygiene education is essential to prevent complications, but its impact is usually limited when it is not reinforced with effective tools. This study aims to evaluate an audiovisual educational tool with reinforcement messages, compared with a verbal explanation about the proper use of the orthodontic oral hygiene kit. Methods: This was a randomized controlled trial that included 62 patients randomly assigned to an intervention group: 31 patients who received an educational video plus three reinforcement messages via WhatsApp, and a control group: 31 patients who received a verbal explanation about orthodontic hygiene. Initial measurement of the O'Leary plaque index was performed, and the measurement was repeated 6 months later. Results: The intervention group showed a mean reduction of 31.16 points, compared to 7.67 points in the control group, with a mean difference between groups of 23.49 points (95% CI: 19.84 to 27.14; p < 0.001). Conclusions: The audiovisual educational tool with reinforcement messages was significantly more effective than the verbal explanation in improving oral hygiene in orthodontic patients.